Whole Genome Re-sequencing and Bulk Segregant Analysis Reveals Chromosomal Location for Papaya Ringspot Virus W Resistance in Squash - Shrestha, Swati; Fu, Yuqing; Michael, Vincent Njung’e; Meru, Geoffrey (Frontiers in Plant Science, 2022)
Squash (Cucurbita moschata) is among the most important cucurbit crops grown worldwide. Plant pathogen, Papaya ringspot virus W (PRSV-W) causes significant yield loss in commercial squash production globally. The development of virus-resistant cultivars can complement integrated disease management and mitigate losses due to viral infections. However, the genetic loci and molecular markers linked to PRSV-W resistance that could facilitate marker-assisted selection (MAS) for accelerated cultivar development are unknown. In this study, quantitative trait loci (QTL), molecular markers, and candidate genes associated with PRSV-W resistance in squash were identified in an F2 population (n = 118) derived from a cross between Nigerian Local accession (resistant) and Butterbush cultivar (susceptible). Whole genome re-sequencing-based bulked segregant analysis (QTLseq method; n = 10 for each bulk) and non-parametric interval mapping were used to identify a major QTL associated with PRSV-W resistance on chromosome 9 (QtlPRSV-C09) (p < 0.05) of C. moschata. QtlPRSV-C09 extended from 785,532 to 5,093,314 bp and harbored 12,245 SNPs among which 94 were high-effect variants. To validate QtlPRSV-C09, 13 SNP markers were assayed as Kompetitive allele-specific PCR (KASP) markers in the F2 population and tested for the association with PRSV-W resistance. Among these, two KASP markers (Ch09_2080834 and Ch09_5023865-1) showed significant association with PRSV-W resistance (p < 0.05). The two SNPs were located within exons of putative disease-resistant genes encoding the clathrin assembly family and actin cytoskeleton-regulatory complex proteins, which are implicated in disease resistance across plant species. The findings of this study will facilitate MAS for PRSV-W resistance in squash and allow further understanding of the functional mechanisms underlying potyvirus resistance in Cucurbita species.